MODEL DEVELOPMENT FOR PROCESS SELECTION THAT CONSIDERS DESIGN AND COST OF CONFORMANCE IN MAKE-TO-ORDER MANUFACTURING SYSTEM - ADAM JERUSALEM (NIM: 23407041), MOHAMMAD
Production activities in a make-to-order manufacturing systems are based on the characteristics of customer order that include production time, product quality or production cost. Off-line and on-line quality controls are needed to assure quality of product design and manufacturing process. These off-line and on-line quality controls are includes prevention cost and appraisal cost, both are known as cost of conformance. With these characteristics the product design and manufacturing process selection become the decision variable. This research is aimed at solving the problems of design and process selection. The developed model is to minimize production cost by integrating problems of design and process selection that considers cost of conformance. Model development includes steps of system description, conceptual model formulation, mathematic model formulation, verification and validation. The production cost is composed of design cost, prevention cost, manufacturing cost, loss of quality, inspection-correction cost, and finishing cost. The model is solved using LINGO v_9.0. The result is used as a basis for calculating tolerance limit and production time. The model is implemented at a small-scale make-to-order manufacturing system producing crimper, a part for candy packaging.